215k views
4 votes
5. Solve 6(x - 1) = 6x - 6​

5. Solve 6(x - 1) = 6x - 6​-example-1
User CallumH
by
4.7k points

2 Answers

6 votes

Answer:

Infinite Solution

Explanation:

Step 1: Simplify both sides of the equation.

6(x−1)=6x−6

(6)(x)+(6)(−1)=6x+−6 (Use Distributive Property)

6x+−6=6x+−6

6x−6=6x−6

Step 2: Subtract 6x from both sides.

6x−6−6x=6x−6−6x

−6=−6

Step 3: Add 6 to both sides.

−6+6=−6+6

0=0

User Ssdehero
by
4.6k points
4 votes

Answer:

Its infinite solutions because its the same exact thing when you simplify the first half of the problem.

Explanation:

User YasirPoongadan
by
5.9k points